Branchinecta fueguina - Cohen, Rosa Graciela (Zenodo, 2008)
Branchinecta fueguina nov. sp. Type material . Deposited in the Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”. Holotype , temporary pond in Tierra del Fuego province (Argentina), 53°47'12'' S, 67°46'55'' W, male number: MACN-In 37498; date: January 23, 2001; collector: M. C. Marinone; Allotype , same collecting data as holotype, female (ovigerous), number: MACN-In 37499. Type locality . temporary pond by Route C, in front of Laguna de los Cisnes, behind Río Grande Airport (53°47'12'' S, 67°46'55'' W), Tierra del Fuego, Antártida e Islas del Atlántico Sur Province, Argentina. Etymology . The specific epithet is a toponym of Tierra del Fuego, from which the specimens came. Description. Male : Mean total length from front to end of the abdomen with uropods (cercopods) without setae: 16.9 mm (16.1–18.1 mm). Mean uropods (cercopods) without setae length: 1.3 mm (1.1–1.4 mm). Average ratio of “head + thorax” to “abdomen + uropods without setae”: 1.02. Pedunculate eye diameter: 0.6–0.7 mm. Antenna 1 as usual, filiform and slender, 2.3–2.8 mm, long. Antenna 1 length is 4 times the diameter of compound eye. Antenna 2 basal article (Figs 1 A–E), 2.7–3.1 mm long (Fig. 1 G), bearing a proximal anteriomedial rough welt provided with sensory setae, projecting beyond basal article anterior surface and visible in dorsal view (Fig.1 F). Welt extending posteriorly and terminating as a conspicuous apophysis (Figs 1 A–E). Apophysis hanging medially from the posteriomedial side of article, proximally swollen until it reaches a heel shaped area (Fig. 1 B), arcing anteriorly, apex rounded. Apophysis and apex posterior surface with cuticular ornamentation and with some scattered sensory setae (Fig. 1 E). Basal article proximomedial half concave and smooth (Figs 1 C, 1E). Basal article distal half with a longitudinal crest produced proximally in a strong blunt medioposteriorly directed point with some scattered small sensory setae. Crest lengthened following the major axis of the article but not reaching its distal end ...